Procedural Options for Measuring Muscle Strength - Mindova S. (Sciendo, 2016)
The aim of the present study was to provide alternative means of measurement and evaluation of muscle strength in rehabilitation practice and diagnostics. In the last few years many electronic devices for evaluation of muscle strength have developed. Contemporary studies have shown that in addition to the standard manual muscle testing muscle strength can be assessed more objectively and analytically using electronic dynamometers and equipment. The strain gauges are used as a tool of precision in the industry that allows measurement of mechanical loads by dynamometers. By using these tools is possible to obtain continuous digital measurement and recording of muscle strength.